2021
DOI: 10.1002/marc.202100286
|View full text |Cite
|
Sign up to set email alerts
|

ThePreparation of Electrospun PVDF/TBAC Multimorphology Nanofiber Membrane and Its Application in Direct Contact Membrane Distillation

Abstract: Microporous membrane with a hydrophobic surface, high porosity, and narrow pore size distribution is the ideal membrane distillation (MD) membrane. The electrospun membranes for MD are a new type and effective way to seawater desalination. Herein, a novel polyvinylidene fluoride (PVDF)/tetrabutylammonium chloride (TBAC) electrospun nanofiber membrane (ENMs) fabricated apply to for direct contact membrane distillation (DCMD). Combine with the spinning condition, the characteristic and content of TBAC significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As the nonsolvent concentration increased, the nanofiber membranes showed the gradually decreased permeate flux ranging from 51.4 to 41.5 kg m –2 h –1 and improved salt rejection ranging from 99.79 to 99.97% (Figure b), which could be induced by the decreased pore size and porosity. Meanwhile, it could be concluded that the GPA-3 membranes exhibited the optimal equilibrium between permeate flux (47.4 kg m –2 h –1 ) and salt rejection (99.97%), which was comparable to the desalination performance of toxic solvent-processed distillation membranes reported previously. ,, We further explored the impacts of salt concentration in feed solutions on the performance of GPA-3 membranes (Figure S13). As the NaCl concentration increased from 1 to 4 wt %, the permeate flux decreased from 50.8 to 45.3 kg m –2 h –1 , which could be related to the reduced water activity attributed to the hydration of ion and concentration polarization in solutions with higher salt contents. ,, As presented in Figure c, the green polyamide membranes showed a significant increase of permeate flux from 4.6 to 129 kg m –2 h –1 while maintaining the almost unchanged salt rejection (∼99.96%), with increasing the feed temperature from 60 to 90 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the nonsolvent concentration increased, the nanofiber membranes showed the gradually decreased permeate flux ranging from 51.4 to 41.5 kg m –2 h –1 and improved salt rejection ranging from 99.79 to 99.97% (Figure b), which could be induced by the decreased pore size and porosity. Meanwhile, it could be concluded that the GPA-3 membranes exhibited the optimal equilibrium between permeate flux (47.4 kg m –2 h –1 ) and salt rejection (99.97%), which was comparable to the desalination performance of toxic solvent-processed distillation membranes reported previously. ,, We further explored the impacts of salt concentration in feed solutions on the performance of GPA-3 membranes (Figure S13). As the NaCl concentration increased from 1 to 4 wt %, the permeate flux decreased from 50.8 to 45.3 kg m –2 h –1 , which could be related to the reduced water activity attributed to the hydration of ion and concentration polarization in solutions with higher salt contents. ,, As presented in Figure c, the green polyamide membranes showed a significant increase of permeate flux from 4.6 to 129 kg m –2 h –1 while maintaining the almost unchanged salt rejection (∼99.96%), with increasing the feed temperature from 60 to 90 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it could be concluded that the GPA-3 membranes exhibited the optimal equilibrium between permeate flux (47.4 kg m −2 h −1 ) and salt rejection (99.97%), which was comparable to the desalination performance of toxic solventprocessed distillation membranes reported previously. 28,29,53 We further explored the impacts of salt concentration in feed solutions on the performance of GPA-3 membranes (Figure S13). As the NaCl concentration increased from 1 to 4 wt %, the permeate flux decreased from 50.8 to 45.3 kg m −2 h −1 , which could be related to the reduced water activity attributed to the hydration of ion and concentration polarization in solutions with higher salt contents.…”
Section: Desalination Performance Of Polyamidementioning
confidence: 99%
“…Furthermore, the resulting The PDA@MWCNTs/PVDF composite support layer comprises the PVDF tree-like nanofiber membrane and PDA@MWCNTs thin film (Figure 2). The preparation process of the PVDF tree-like nanofiber membrane is detailed in our previous experimental work [29]. In this study, we fabricated three different composite support layers by changing the content of PDA@MWCNTs.…”
Section: The Morphology and Properties Of Pda@mwcnts/pvdf Support Mem...mentioning
confidence: 99%
“…[41] Surfactant additives, i.e., tetrabutylammonium chloride (TBAC) and benzyltriethylammonium chloride (BTAC) were used for altering the external morphology of fibers and changing the internal structure of the membrane fabric. [40,50,54] For instance, Li et al [40] added TBAC, a cationic surfactant, into PVDF to increase the electrical conductivity of the polymer solution and create a repulsion effect on the jet streams. [40] Subsequently, the jets are split, forming a branched structure and a tree-like nanofibrous membrane, as illustrated in Figure 5.…”
Section: Addition Of Additives In the Spinning Solutionmentioning
confidence: 99%